Foraging Behaviour and Feeding Success of the Black Ibis (Pseudibis papillosa) Inhabiting Rural and Urban Area of churu City, Rajasthan, India - A. N. Sharma1; V. C. Soni2, K. C. Soni1* (Recent Research in Science and Technology, 2010)
Foraging behaviour and feeding success of the Black ibis (Pseudibis papillosa) were studied during 2003 - 2006 in the rural and urban area of Churu city, Rajasthan, India. The bird is chiefly non visual tactile forager and exhibits various types of feeding behaviour viz. probing (shallow, deep, stepping, stationary and multiple), standing, walking, running, groping, pecking, standing fly catching, bill dragging and flipping. The studies were conducted in seven different microhabitats to which the birds were frequent visitors. They were waste water body (WWB), municipal garbage dumping station (MGDS), animal dead body dumping station(ADBDS), agriculture field (AF), sand dune (SD), forest area (FA) and grazing field (GF).The Black ibis also follows seasonal selection of various microhabitats depending on the food availability. As such the birds were found in the flock of 5 to 15 at the carcasses center in the winter season. Solitary (singleton) feeding was also noted at the municipal garbage dumping station, waste water bodies and sand dunes during aforesaid season. Contrary to this the Black ibis (Pseudibis papillosa) either solitary or in flocks of 5 to 7 feeds exclusively in the agriculture fields and grass lands during the rainy season. However, the bird either solitary or in small flocks of 3 to 7 occupy wide varieties of microhabitats during the summer season viz. sand dunes, waste water bodies, municipal garbage dumping station and carcasses center etc. Moreover, the feeding in the garbage and muddy shore of waste water pond are the common feature throughout the year.